2005
DOI: 10.1109/lpt.2005.852321
|View full text |Cite
|
Sign up to set email alerts
|

High-power GaN-mirror-Cu light-emitting diodes for vertical current injection using laser liftoff and electroplating techniques

Abstract: A large-area (1 x 1 mm) vertical conductive GaN-mirror-Cu light-emitting diode (LED) fabricated, using the laser liftoff and electroplating techniques is demonstrated. Selective p-GaN top area. was first electroplated by the thick copper film, and then an excimer laser was employed to separate the GaN thin film from the sapphire substrate. The luminance, intensity of the vertical conductive p-side-down GaN-mirror-Cu LED presented about 2.7 times in magnitude as compared with that of the original GaN-sapphire L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
30
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(30 citation statements)
references
References 10 publications
0
30
0
Order By: Relevance
“…VLEDs are considered to be the candidates for the future high-power and high-efficiency LED devices attributed to their advantages of better current injection and excellent heat dissipation. [1][2][3] Surface texturization of the Laser lift off (LLO) exposed N-polar GaN by etching in alkali (as KOH) or acid (as H 3 PO 4 ) etchant is an effective and commonly adopted way to improve the optical power of VLEDs by eliminating the total internal reflectance (TIR). By comparing the different etching characteristics of Ga-polar and N-polar GaN, Li et al 4,5 has concluded that it was only due to the different states of surface bonding.…”
Section: Introductionmentioning
confidence: 99%
“…VLEDs are considered to be the candidates for the future high-power and high-efficiency LED devices attributed to their advantages of better current injection and excellent heat dissipation. [1][2][3] Surface texturization of the Laser lift off (LLO) exposed N-polar GaN by etching in alkali (as KOH) or acid (as H 3 PO 4 ) etchant is an effective and commonly adopted way to improve the optical power of VLEDs by eliminating the total internal reflectance (TIR). By comparing the different etching characteristics of Ga-polar and N-polar GaN, Li et al 4,5 has concluded that it was only due to the different states of surface bonding.…”
Section: Introductionmentioning
confidence: 99%
“…The use of electroplating technology has improved the performance of GaN-based LEDs in solid-state lighting applications [1][2][3][4]. However, using electroplating technology adds an extra process to LED manufacturing because laser lift-off (LLO) technology must be used, causing LED manufacturers have low throughput, low yield, and high cost.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, vertical InGaN/GaN LEDs have attracted much attention due to the improvement of the light extraction efficiency and heat release from the devices [3]. These improvement of vertical LEDs performance is attributed to the p-type reflector on p-GaN layer, which reflects light generated from the active region to top surface and effectively transfers the heat from p-n juction to package.…”
Section: Introductionmentioning
confidence: 99%